Associations between parental socioeconomic status and child brain electrophysiology - Runola, Riikka (My University, 2023)
Parental socioeconomic status influences children’s growth environment and is associated with child’s later-life outcomes. Due to the conditions that socioeconomic status offer, the brain of low socioeconomic status children tends to develop faster than the high socioeconomic status children’s brain. Human brain electrophysiological signals express both periodic and aperiodic activity. Unlike aperiodic activity, periodic activity has been widely studied and connected to many physiological, cognitive, and disease states. Lately, also aperiodic activity has been shown to reflect physiological information. The aperiodic parameters (broadband offset and exponent) have been linked to brain maturation. This study estimated the association between 3-year-old children's (n=58) EEG (electroencephalography) and parental socioeconomic status. The aperiodic activity changes while aging as brain activity becomes more-and-more adult-like. Also, according to a theory, low socioeconomic status children’s brain tends to develop faster. Based on this, we hypothesized that low socioeconomic status children’s aperiodic activity would be more adult-like at 3 years of age than high socioeconomic status children’s aperiodic activity. The results show a significant association between family socioeconomic status and child aperiodic offset. Confounding factors, such as the child’s age, sex, and gestational age did not affect the results. As the socioeconomic status increases, the aperiodic offset decreases, that is, parental high socioeconomic status was associated with more adult-like aperiodic brain electrophysiology. In addition, there was a significant association between aperiodic offset and child sex. Our main result contrast with previous findings about low socioeconomic status being associated with faster brain development. However, the study sample consisted of a less-studied age group of 3-year-olds, and the sample was narrow in age. More research is needed to understand to what extent SES can affect an individual’s development and later life outcomes.
Keywords: socioeconomic status, brain electrophysiology, EEG